The Online Feedback to Online Backfeed in Writing - Dodi Erwin Prasetyo (English Education : English Journal for Teaching and Learning, 2026)
The writing skill is by rehearsal. The process of writing in the academic context cannot be autodidact learned. In addition, this era emerges the technological usage within the teaching and learning. Those acquire complex obstacles in learning writing. Therefore, this paper aimed at finding to exploring urgencies and delineation of e-writing, defining online feedback and online backfeed, then compounding between online feedback and online backfeed for learning writing skill. Suggestions are provided for the pedagogical aspects and future researches. For the pedagogical aspects, the curriculum developer, teachers, and the technological experts have to discuss together to produce more effective educational processes, and outputs in term of curriculum, syllabus, lesson plan, teaching media and so forth. Meanwhile for future researches, it requires further observations to gather more comprehensive process and outputs.